Research on Malaysia's science and technology innovation policy: R&D and investment in the manufacturing sector / Hui-Nee Au-Yong, Vikneswari Vija Kumaran and Thavamalar Ganapathy - Hui-Nee, Au-Yong; Vija Kumaran, Vikneswari; Ganapathy, Thavamalar (UiTM Cawangan Johor, 2023)
This paper intends to review the implementation of Science, Technology and Innovation (STI) on industries and its competitiveness. The main STI Policies include the STI Master Plan 2020-2030. The Government has established several STI government agencies to promote STI including Malaysian Technology Development Corporation (NITDC), Malaysian Industry-Government Group for High Technology (WGHT), MylPO and Collaborative Research in Engineering, Science and Technology (CREST). For high value-added industries and science and technology parks, several industrial parks have been set up, including the Kulim High-Tech Park (KHTP), Technology Park Malaysia (TPM), MSC Malaysia, Senai High-Tech Park, Penang Science Park and North Penang Science Park. In terms of high-tech research and development investments in firms, Malaysia ranked fourth as manufacturing hub places, Malaysia is ahead from other countries in Asia. In the industry, there are NWCs, mostly from the USA, EU, Japan and other Asian countries i.e. South Korea, China and Taiwan. Among the government-linked companies (GLCs) investing in R&D are Petronas and Sime Darby. R&D investments are identified in the automobile sector and E&E cluster. sufficient integration on the innovation culture within local businesses should be instituted. As a windup, future improvement should integrate the enhancement of STI awareness and match the needs of innovation-led development. Keywords: Foreign Direct Investment, Manufacturing, Research and Development, Science, Technology and Innovation Policy, Technology Transfer.